Inheritance Rights of Wives and Children in Siri Marriages: Community Perspectives and Legal Implications in Silandoyung Village - Nurliana, Nurliana; Siddiq T, Ibnu Radwan (Prodi Studi Agama-Agama, 2025)
This study investigates the inheritance rights of wives and children in unregistered (siri) marriages within the community of Silandoyung Village, Silau Kahean District, Simalungun Regency. Using an empirical socio-legal approach, the research combines field interviews with village officials, religious leaders, traditional leaders, and affected families, alongside a normative analysis of Islamic law, the Compilation of Islamic Law (KHI), and Indonesian positive law. The findings reveal that the community acknowledges inheritance rights for wives and children from siri marriages based on religious values and customary norms, despite the absence of state recognition due to the lack of official marriage registration. This discrepancy creates potential inheritance disputes, reflecting a legal tension between religious-customary legitimacy and state law. From the perspective of Islamic law, siri marriages are valid if their pillars are fulfilled, granting wives and children inheritance rights; however, under Indonesian positive law, registration is mandatory for legal recognition. The study concludes that marriage registration is not merely an administrative formality but a crucial mechanism to harmonize state law with local wisdom, thereby ensuring legal protection and justice for women and children in siri marriages.